Investigating the presumed causal links between drought and dzud in Mongolia - Sternberg, T. (Natural Hazards, 2017)
Extreme weather events present environmental and social challenges across the Eurasian steppe. In Mongolia much attention is given to drought and dzud (severe winter conditions) impact on rural livelihoods, landscapes and governance. A link between the two events, fostered by international and state agencies, speculates that drought leads to dzud; this has become the widely accepted doctrine. However, the relationship between the two events is assumed rather than analysed. Whilst there may be natural links between climate events, causality is more difficult to establish yet often claimed post-event. This paper stresses Mongolia’s destructive dzuds of 1999–2001 and 2009–2010 in examining drought frequency before dzud events. Findings question the hazard connection as just 3 of 32 examined dzud events were preceded by drought. Investigation did not document a relationship between the disasters; linkages between extreme events were implied rather than established. The human role in disaster also needs to be assessed as preparation, and response are key factors for mitigation. Study results identified a lack of causality between the disasters, suggesting more assiduous investigation of hazards is needed in Mongolia. This can clarify causal factors, identify risk and improve disaster mitigation strategies in Mongolia.